Lipopolysaccharide Attenuates Induction of Proallergic Cytokines, Thymic Stromal Lymphopoietin, and Interleukin 33 in Respiratory Epithelial Cells Stimulated with PolyI:C and Human Parechovirus - Lin, Tsang-Hsiung; Cheng, Chih-Chi; Su, Hsing-Hao; Huang, Nan-Chieh; Chen, Jih-Jung; Kang, Hong-Yo; Chang, Tsung-Hsien (Frontiers in Immunology, 2016)
Epidemiological studies based on the “hygiene hypothesis” declare that the level of childhood exposure to environmental microbial products is inversely related to the incidence of allergic diseases in later life. Multiple types of immune cell-mediated immune regulation networks support the hygiene hypothesis. Epithelial cells are the first line of response to microbial products in the environment and bridge the innate and adaptive immune systems; however, their role in the hygiene hypothesis is unknown. To demonstrate the hygiene hypothesis in airway epithelial cells, we examined the effect of lipopolysaccharide (LPS; Toll-like receptor 4 ligand) on the expression of the proallergic cytokines thymic stromal lymphopoietin (TSLP) and interleukin 33 (IL33) in H292 cells (pulmonary mucoepidermoid carcinoma cells). Stimulation with the TLR ligand polyI:C and human parechovirus type 1 (HPeV1) but not LPS induced TSLP and IL33 through interferon (IFN) regulatory factor 3 (IRF3) and NFB activity, which was further validated by using inhibitors (dexamethasone and Bay 11-7082) and shRNA-mediated gene knockdown. Importantly, polyI:C and HPeV1-stimulated TSLP and IL33 induction was reduced by LPS treatment by attenuating TANK-binding kinase 1, IRF3 and NFB activation. Interestingly, the basal mRNA levels of TLR signaling proteins were downregulated with long-term LPS treatment of H292 cells, which suggests that such long-term exposure modulates the expression of innate immunity signaling molecules in airway epithelial cells to mitigate the allergic response. In contrast to the effects of LPS treatment, the alarmin HMBG1 (high mobility group protein B1) acts in synergy with polyI:C to promote TSLP and IL33 expression. Our data support part of the hygiene hypothesis in airway epithelia cells in vitro. In addition to therapeutic targeting of TSLP and IL33, local application of non-pathogenic LPS may be a rational strategy to prevent allergies.